Correction: Facile preparation of phospholipid–amorphous calcium carbonate hybrid nanoparticles: toward controllable burst drug release and enhanced tumor penetration. Issue 73 (7th September 2020) - Wang, Cheng; Liu, Xuerong; Chen, Shaoqing; Hu, Fuqiang; Sun, Jihong; Yuan, Hong
Abstract : Correction for 'Facile preparation of phospholipid–amorphous calcium carbonate hybrid nanoparticles: toward controllable burst drug release and enhanced tumor penetration' by Cheng Wang et al., Chem. Commun., 2018, 54, 13080–13083, DOI: ; 10.1039/C8CC07694D .